A influência do arranjo institucional nos mecanismos de governança e nos relacionamentos interorganizacionais em uma aglomeração de empresas: utilizando a teoria dos arranjos institucionais como referência de análise - Osmar Vieira de Souza Filho (2015)
This thesis aims to analyze the relationship between the characteristics of the institutional arrangement and the use of governance mechanisms for managing the relationships in a clustering environment, trying to understand how agents decide by relating to each other in supply networks. The theoretical argument is based on the Theory of Institutional Arrangements and Transaction Cost Economics. The empirical case that illustrates the discussion was an agglomeration of whey producers located in Minas Gerais State. Based on the general and specific objectives of this research, it was developed a multiple case study involving thirteen dairy companies located in the region of the Campo das Vertentes. The study was qualitative and descriptive in its nature. The procedure used for data collection was the application of semi-structured interviews, using a semi-structured questionnaire as the instrument. The units of analysis were the relations between the companies and the units of observation were the companies. For data analysis, we used the Framework Method for the description of the causes of transaction costs, the governance mechanisms and characteristics of institutional arrangement, and the Qualitative Comparative Analysis of Fuzzy Sets (fsQCA) for the analysis of relations between the characteristics of the institutional arrangements and the adoption of governance mechanisms. The main conclusion is that the analytical tool of the Theory of Institutional Arrangements serves as an advanced feature to identify the existence of drivers and facilitators for the formation of cooperative agreements between companies in agglomerations. In addition, deepens on how instituttions influence the relationship characteristics between companies. Cooperation in relationships in agglomerations will be possible only if the characteristics of institutional arrangements are favorable to the execution of these agreements. The intensification of the interactions between the participants of the arrangement is dependent on the existence of a flow of information established between them, which works as both driver and facilitator of cooperative relationships. The study allows one to conclude that understanding the relationship between the characteristics of the institutional arrangement, the causes of transaction costs and the mechanisms of governance, enables the analysis of the aspects that structure and define a collective decision-making, the roles and functions of the actors involved, and the relationships that are established in cooperative arrangements. Understanding these dynamics is essential to understand the governance and the relationships in situations of horizontal interdependencies between heterogeneous actors.